A Review of Elliptic Flow of Light Nuclei in Heavy-Ion Collisions at RHIC and LHC Energies - Md. Rihan Haque; Chitrasen Jena; Bedangadas Mohanty (Advances in High Energy Physics)
We present a review of the measurements of elliptic flow (v2) of light nuclei (d, d¯, t, He3, and He¯3) from the RHIC and LHC experiments. Light (anti)nuclei v2 have been compared with that of (anti)proton. We observed a similar trend in light nuclei v2 to that in identified hadron v2 with respect to the general observations such as pT dependence, low pT mass ordering, and centrality dependence. We also compared the difference of nuclei and antinuclei v2 with the corresponding difference of v2 of proton and antiproton at various collision energies. Qualitatively they depict similar behavior. We also compare the data on light nuclei v2 to various theoretical models such as blast-wave and coalescence. We then present a prediction of v2 for He3 and He4 using coalescence and blast-wave models.